PERBEDAAN TINGKAT PERCEIVED RISK, FEAR OF CRIME, DAN MEKANISME COPING PADA MASYARAKAT YANG BERAKTIVITAS DI WILAYAH RAWAN TINDAK KEJAHATAN - Fahmi, Teuku (JURNAL SOSIOLOGI, 2014)
Increasing the news about crimes committed in the province of Lampung, consciously or not, affect the pattern of community life. Many aspects (activities) productive hampered by fear are caused. The real implications of the rise of the news that is the limited / inhibition of community activities in public spaces or simply to mobilize someplace. This study illustrates the differences in the level of perceived risk, fear of crime, and community coping mechanisms that move in the two regions with the highest crime rate in the province of Lampung. The approach used in this research is quantitative, while the research method used is described and an explanatory. The number of samples in this study amounted to 80 people who are living and active communities in two districts / cities in Lampung province that has the highest crime rate. The results of different test (two independent samples test - Mann Whitney) were conducted on three variables show that that there are differences in the level of perceived risk, fear of crime, and significant coping mechanism between perceptional respondents who move in North Lampung and in Bandar Lampung (the calculation in three variables Asymp Sig <0.05). Referring to the descriptive overview of the response variable in all three assessments indicates that respondents who move in North Lampung give a higher assessment category compared with respondents who move in Bandar Lampung. In this case, the circumstances in Bandar Lampung tend to be more favorable in terms of safety aspects when compared with North Lampung.